1960
DOI: 10.1111/j.1748-1716.1960.tb01957.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulatory Data in Normal Subjects at Rest and During Exercise in Recumbent Position, with Special Reference to the Stroke Volume at Different Work Intensities

Abstract: Right heart catheterization has been performed in 18 healthy subjects, 14 males and 4 females, including estimation of cardio‐vascular pressures and cardiac output at rest and during different intensities of exercise in recumbent position. During exercise the cardiac output increased linearly with the oxygen uptake. The increase of the arterio‐venous oxygen difference in relation to the work load or the pulse rate was higher in the males than in the females. With change from rest to work the stroke volume incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
2

Year Published

1963
1963
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(70 citation statements)
references
References 18 publications
3
65
2
Order By: Relevance
“…A normal response, as observed in our control group, should have been a small increase as reported unaniMOusly. 13 15,18,21,23,30 In patients with medium or large shunts, however, Q, determinations and thus estimation of stroke volume may have been inaccurate because only one sample of blood from the right atrium was used for determining oxygen content in mixed venous blood.3' However, this problem is of minor importance in group 1 subjects who had closed or minor defects. Furthermore, only marginal differences between exercise right atrial and pulmonary arterial oxygen saturations were observed in the control group (mean 2% units, range 0 to 3).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A normal response, as observed in our control group, should have been a small increase as reported unaniMOusly. 13 15,18,21,23,30 In patients with medium or large shunts, however, Q, determinations and thus estimation of stroke volume may have been inaccurate because only one sample of blood from the right atrium was used for determining oxygen content in mixed venous blood.3' However, this problem is of minor importance in group 1 subjects who had closed or minor defects. Furthermore, only marginal differences between exercise right atrial and pulmonary arterial oxygen saturations were observed in the control group (mean 2% units, range 0 to 3).…”
Section: Discussionmentioning
confidence: 98%
“…Supine exercise testing was performed on an Elema electrically braked bicycle, with the legs slightly elevated as described by Holmgren et al 13 The load during the study was Symptoms and PASP >30 mm Hg (2) No symptoms (2) History of bacterial endocarditis (2) Symptoms only (3) Minor (n 1) Dyspnea (1) Symptoms only (1) PASP pulmonary arterial systolic pressure. Closed oxygen uptake (ml/min) and arteriovenous oxygen difference (ml/min) between the aorta and pulmonary artery, and Q, (systemic flow, liters/min) was calculated from the oxygen uptake and arteriovenous oxygen difference between the aorta and right atrium.…”
Section: Methodsmentioning
confidence: 99%
“…During peak exercise, the athletes achieved a greater mean maximal heart rate (p < 0.01); this difference was probably related to differences in age and in motivation between the two groups, and is consistent with previous circulatory changes during exercise for athletes2 and for untrained subjects. 3 Of particular interest are the ventricular volumes during exercise. Although the exercise increase in cardiac output is related to increased heart rate and stroke volume,2 8-10 the actual mechanism responsible for the increase in stroke volume remains controversial.…”
Section: Resultsmentioning
confidence: 99%
“…Influence of sex, geographical origin, exercise method and position on Ppa Sex and the geographical origin of the data did not significantly influence resting and exercise P pa values (online data supplement, tables G-I) [13,14,16,18,19,29,35,39,43,47].…”
Section: Pulmonary Arterial Pressure During Exercisementioning
confidence: 99%